2010
DOI: 10.1097/ccm.0b013e3181cb0888
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care unit alarms—How many do we need?*

Abstract: This study used a new approach of off-line, video-based physician annotations, showing that even with modern monitoring systems most alarms are not clinically relevant. As the majority of alarms are simple threshold alarms, statistical methods may be suitable to help reduce the number of false-positive alarms. Our study is also intended to develop a reference database of annotated monitoring alarms for further application to alarm algorithm research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
114
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(128 citation statements)
references
References 13 publications
7
114
1
4
Order By: Relevance
“…Four of the studies were conducted in pediatric populations 5,[20][21][22] and 7 were conducted in adult populations. [23][24][25][26][27][28][29] One study included both children and adults. 30 Additionally, in 1 study, 5 alarms in both a pediatric general care area and a pediatric ICU were annotated; for this review, we used only pediatric ICU data.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the studies were conducted in pediatric populations 5,[20][21][22] and 7 were conducted in adult populations. [23][24][25][26][27][28][29] One study included both children and adults. 30 Additionally, in 1 study, 5 alarms in both a pediatric general care area and a pediatric ICU were annotated; for this review, we used only pediatric ICU data.…”
Section: Resultsmentioning
confidence: 99%
“…Both cases compete for alarm fatigue and put patient safety at risk (6,9) . In this sense, the proper programming of alarms to the individual needs of patients has to be immediately incorporated into the routine of nursing.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, scholars and researchers warn of a phenomenon that incites an even bigger concern: alarm fatigue (6) . Alarm fatigue is defined as the phenomenon that occurs when a very large number of alarms covers the clinically significant ones, enabling alarms of clinical relevance to be disabled, silenced and ignored by the team (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found alerts from monitoring systems in an ICU and emergency department environment to be tremendously frequent and with an extremely high false-positive rate. [17][18][19][20][21] Unsurprisingly, it has been reported that only about 10% of alerts are responded to by the clinical staff. 22 In an attempt to improve alert relevancy and accuracy, newly designed integrated monitoring systems for ICUs use alert algorithms and trend analysis performed on data received from multiple vital signs monitors.…”
Section: Discussionmentioning
confidence: 99%